2001
DOI: 10.1038/35098053
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale imaging of insulating diamond through resonant electron injection

Abstract: The electronic properties of insulators such as diamond are of interest not only for their passive dielectric capabilities for use in electronic devices, but also for their strong electron confinement on atomic scales. However, the inherent lack of electrical conductivity in insulators usually prevents the investigation of their surfaces by atomic-scale characterization techniques such as scanning tunnelling microscopy (STM). And although atomic force microscopy could in principle be used, imaging diamond surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(85 citation statements)
references
References 18 publications
5
80
0
Order By: Relevance
“…5c shows a resonance tunneling behaviour, similar to the one observed for clean diamond surfaces in Ref. [12,13]. Nevertheless, in our case, the surface resonances are observed for the hydrogenated surface, containing also residual oxygen atoms while in ref [13], hydrogen-free, 2×1 reconstructed surfaces have been studied.…”
Section: Surface Morphologymentioning
confidence: 56%
See 3 more Smart Citations
“…5c shows a resonance tunneling behaviour, similar to the one observed for clean diamond surfaces in Ref. [12,13]. Nevertheless, in our case, the surface resonances are observed for the hydrogenated surface, containing also residual oxygen atoms while in ref [13], hydrogen-free, 2×1 reconstructed surfaces have been studied.…”
Section: Surface Morphologymentioning
confidence: 56%
“…Even though similar experiments have been done before, there are several novelties in our measurements compared to previous work [12,13]. Compared to results of Dujardin and Bobrov [12,13] we use undoped H terminated CVD diamond films (in all other published cases either B-doped samples or clean surfaces with a Penney reconstructed surface have been used for STM imaging providing sufficient surface conductivity). Till now, as far as we know it was not possible to carry out STM atomic resolution imaging on annealed Hterminated undoped diamond films.…”
Section: Surface Morphologymentioning
confidence: 80%
See 2 more Smart Citations
“…Because of the applied electric field between STM tip and sample, the ISs shift to higher energies and their energy spacings expand. It has been demonstrated that tunneling via ISs allows detailed visualization of the surface of insulating diamond films with atomic resolution [8]. IS dynamics has recently been investigated for various flat surfaces, including Fe [9], Au [10] and Cu surfaces [10,11].…”
mentioning
confidence: 99%